A Combined Approach for the Aesthetic Management of Stained Enamel Opacities: External Bleaching Followed by Resin Infiltration - O. Marouane; N. Douki; F. Chtioui (Case Reports in Dentistry)
Stained enamel opacities are frequently encountered in dental practice. However, due to the risk of unaesthetic outcome, managing such lesions by resin infiltration techniques alone is not advised. Therefore, performing external bleaching before resin infiltration procedure is mandatory to eliminate stains from the hypomineralized lesions in order to aesthetically infiltrate them. In this work, we describe clinical cases in which external bleaching and resin infiltration techniques were used for managing stained enamel hypomineralized lesions related to traumatic dental injuries and molar incisor hypomineralization. Despite the fact that this approach has some limitations, it could be concluded that external bleaching associated with the resin infiltration technique shows promising results to aesthetically manage stained enamel opacities when the stain is totally removed after bleaching.